Upaya Forum Kerukunan Umat Beragama Tapanuli Selatan dalam Melestarikan Budaya Moderasi Beragama pada Masyarakat Tapanuli Selatan - Hidayat, Arifin; Sitompul, Jamilah (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2024)
The development of religious harmony is part of the harmony of society and the nation, which must be realized, maintained and developed. The formation of religious harmony is part of the practice of religious teachings and the values of Pancasila as the Indonesian people's philosophy of life. Apart from that, it is also to avoid loss of life and property, as has happened to several regions in Indonesia and several parts of the world. In the Joint Regulations of the Minister of Religion and Minister of Home Affairs Number 9 of 2006 and number 8 of 2006 in chapter 2 article 4 it is emphasized that maintaining religious harmony in the Regency/City is the duty and obligation of the Regent/Mayor. So through these duties and obligations a religious harmony forum was formed which became the pioneer and driving force to maintain religious harmony. Through the movement of the Ministry of Religion of the Republic of Indonesia which stated that Indonesian people should have an attitude of religious moderation in harmony with religious harmony forums that aim to maintain religious harmony in Indonesia. So don't hope that forums for religious harmony can provide understanding to the public in maintaining religious harmony, especially in the frame of religious moderation.